Molybdenum Induces the expression of a protein containing a new heterometallic Mo-Fe cluster in desulfoVibrio alaskensis - Rivas, Maria G. (2013)
Biochemistry. 2009 Feb 10;48(5):873-82. doi: 10.1021/bi801773t.